The Hubble Space Telescope - Morey, Allan (Minneapolis, MN : Bellwether Media, Inc., 2018)
"Engaging images accompany information about the Hubble Space Telescope. The combination of high-interest subject matter and light text is intended for students in grades 2 through 7"--
The Hubble Space Telescope at work! -- What is the Hubble Space Telescope? -- The parts of the Hubble Space Telescope -- Hubble Space Telescope missions -- Hubble Space Telescope profile with specs.
Includes bibliographical references and index.
Ages 7-12.
Grades 2 through 7.
Keywords: Hubble Space Telescope (Spacecraft) -- Juvenile literature; Space telescopes -- Juvenile literature; Outer space -- Exploration -- Juvenile literature